Wodą w mur lub wyjście przez okno z betonu. O kilku graffiti Banksy'ego - Mrozewicz, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
Water on the wall or exit through the concrete window. On some graffiti of Banksy The paper discusses a series of five graffiti pieces made in 2005 on the Israeli-Palestinian separation barrier by the English street artist Banksy. Location is here key to the understanding of the messages. The departure point for my analyses is, on the one hand, the meaning connoted with the ‘wall,’ the aim of which is to separate two peoples in a conflict, and, on the other, the representations of landscapes, often with water, painted by Banksy in most of the works. To answer what symbolic role landscape plays in the conflict-ridden area, I look at some other art works, made by contemporary Israeli artists for whom place, landscape and the related question of identity and belonging seem to play a central role. Painted by Banksy on the Palestinian side, the utopian, Eden-like sights, which ‘make holes’ in the concrete barrier, undermine, in an ironic fashion, the hierarchical discourse of power relations constructed by the ‘opposite’ side, and give ‘water’ to the evicted.